Mengoptimalkan pengambilan keputusan dalam perbankan Islam: Peran penting analisis risiko - Kumala, Alfaina Dica Putri (Maliki Interdisciplinary Journal, 2024)
This study discusses the benefits of risk analysis in Islamic banking business decision making. Risk analysis is essential for the continued operation of the business and success of Islamic banks. Risk analysis identifies, evaluates, and categorizes the various types of risks faced by Islamic banks. This includes implementing several strategies such as portfolio diversification, credit management, and an effective internal control system. Efficient risk management enables Islamic banks to comply with related regulations, particularly those governing the Financial Services Authority (OJK) and Bank Indonesia (BI). Risk analysis can help Islamic banks better manage their funds and improve operational efficiency. This can be achieved by identifying and eliminating unnecessary processes, as well as by utilizing the right technology to automate risk management operations. Risk management is a significant improvement in business management as it protects the assets and value of the company while ensuring compliance with Shariah laws and principles